Analytic stability criteria for edge MHD oscillations in high performance ELM free tokamak regimes. (8th November 2017) - Brunetti, D.; Graves, J.P.; Lazzaro, E.; Mariani, A.; Nowak, S.; Cooper, W.A.; Wahlberg, C.
Abstract: A new dispersion relation, and associated stability criteria, is derived for low- n external kink and infernal modes, and is applied to modelling the stability properties of quiescent H-mode like regimes. The analysis, performed in toroidal geometry with large edge pressure gradients associated with a local flattening of the safety factor, includes a pedestal, sheared toroidal rotation and a vacuum region separating the plasma from an ideal metallic wall. The external kink-infernal modes found here exhibit similarities with experimentally observed edge harmonic oscillations.